Reaction of grasspea germplasm resistant to rust and powdery mildew diseases - Shahiduzzaman, M; Mallick, SR; Das, AK (Bangladesh Journal of Agricultural Research, 2018)
Abstract not available Bangladesh J. Agril. Res. 43(3): 525-532, September 2018